FORMATION OF SOFT SKILLS IN TRANSLATION ACTIVITIES - Abduganiyeva Jamilya Rustamovna (Western European Studies, 2024)
The article analyzes the need for developing soft skills among translators based on the current demand of the labor market. In light of the professional translator standard being developed, which aims to formalize and fix the levels of requirements for professional competencies, it seems important to take into account the request for integrative activities in accordance with the new realities of the translation services market and the emphasis on such universal qualities as communication skills, self-management, teamwork, critical thinking, knowledge of project technology, creativity, flexibility. Separately, the article touches upon the criteria for assessing the results of practice; As additional factors that qualitatively influence the assessment, it is proposed to consider the student’s actual acceptance of the functions of coordinator of a group translation project or the successful search and completion of a translation order as a freelancer
Keywords: soft skills; competencies; project technology; labor market